Why is Papua's human development lagging behind? a comprehensive study of education, health, and welfare - Raihannabil, Syfriza Davies; Ananda, Rizhieq Dwi; Kesumawijaya, Anak Agung Istri Anggita; Nabila, Chulia Rachma; Khairani, Nadita (MID Publisher International, 2025)
This study analyzes the determinants of the Human Development Index (HDI) in Papua Province, which continues to lag behind other regions and has not yet met the 2024 RPJMN target, consisting of expected and mean years of schooling as an education indicator, life expectancy as a health indicator, and per capita expenditure as a welfare indicator. The data used comes from BPS in the form of secondary data. This research method uses multiple linear regression analysis. Research shows that increasingly secure education, health, and welfare significantly increase HDI. These findings emphasize the importance of strengthening policies in the fields of education, health, and economic welfare to accelerate human development in Papua. The main contribution of this study is to provide up-to-date empirical evidence on human development disparities at the district/city level in Papua Province, as well as identify priorities for more targeted policy interventions.